THE EFFECT OF TRAINING IN THE IMPROVEMENT OF EMPLOYEE EFFICIENCY IN PHARMACEUTICAL INDUSTRY AND AN APPLICATION - AYDOÄžDU, Sinem (Department of Management, Faculty of Economics and Business, Brawijaya University, 2012)
Businesses faces with important and rapid changes. This rapid change in the business environment forces the organizations to change their operations and structures. Adopting these changes fast and contionus renewal of both employees and organizations help organizations reach the set goals and survive in the competitive market. To be accomplished in competition, companies need well trained and well developed employees from front employees to the top level managers in the executive suite. Moreover, training process must gain continuity. Especially, in Pharmaceutical Industry, due to the fast and rapid changes and improvements concerning the regulations and procedures of Ministery of Health, guidelines such as GMP (Good Manufacturing Practises), GLP (Good Laboratory Practises), GDP (Good Documentation Practises) etc. employees who are working should be trained and updated about the current knowledge to increase the efficiency in the organization. Vice versa, organizations can not raise their competition power in order to exist and develop themselves. To sum up, globalization, fast changes in regulations and procedures and also technological shifts lead to changes even in organizations. In order to cope with these changes, companies need to train their employees. The main purpose of this study is to investigate the effect of training on employee efficiency. Research is carried out with 74 employees from a pharmaceutical company in Istanbul, Turkey. The results of the study support the hypotheses. There a significant difference between white collar and blue collar employees on the idea of efficiency of training in the area of career development, area of productivity, professional growth and customer satisfaction.